Impact of ST-segment elevation on the outcome of Takotsubo syndrome - Gietzen, Thorsten; El-Battrawy, Ibrahim; Lang, Siegfried; Zhou, Xiao-Bo; Behnes, Michael; Ansari, Uzair; Borggrefe, Martin; Akın, Ibrahim (Therapeutics and clinical risk management, 2019)
Impact of ST-segment elevation on the outcome of Takotsubo syndrome